Thermal injury induces early blood vessel occlusion in a porcine model of brass comb burn - Jing Wang (Nature Portfolio, 2021)
Abstract Burn wound progression is an important determinant of patient morbidity and mortality after injury. In this study, we used the brass comb contact burn to determine burn wound vertical injury progression with a focus on blood vessel occlusion and endothelial cell death. Class A 3-month-old Yorkshire pigs received a brass comb contact burn. Burn wounds were sampled at 0, 30 min, 1, 2, 4, and 24 h. Hematoxylin Phloxin Saffron staining and vimentin immunostaining were performed to determine the depth of blood vessel occlusion and endothelial cell death, respectively. The depth of blood vessel occlusion increased by 30 min (p < 0.005) and peaked by 1 to 4 h (p > 0.05). The depth of endothelial cell death risen to a plateau at 30 min (p < 0.005) to 2 h and then peaked at 24 h (p < 0.03). We observed a progression of blood vessel occlusion and vascular endothelial cell death from the middle of the dermis to the hypodermis within 2 h to 4 h after the initial injury, namely a progression from a second-degree (partial thickness) to third-degree (full thickness) burn. These data suggest that therapeutic interventions during this time window may provide a better outcome by reducing or preventing vertical progression of blood vascular occlusion or endothelial cell death.